ENTRE: LITERATURE AS A SPARK TO A POETIC WORK (Palíndromo, 2019)
This article investigates my own recent artistic production, establishing relationships between the visual arts and literature and their creative strategies, whereas the work involved here has the book “If a Traveler on a Night of winter”, by Italo Calvino, as a starting point. Relating author’s own ideas and my observations on the novel, in addition to Maurice Blanchot’s writings on literature, I try to deepen my understanding of my recent poetic production and the role the text has acquired in this visual production.
Keywords: drawing; literature; fragment; Italo Calvino